Deixis types found in Islamic songs by Maher Zain - Nuraini, Eka Indah; Karimah, Rihlatul; Virgiyanti, Diska Fatima; Fachriza, Aries; Dipta, Dinar (Journal of Research on English and Language Learning (J-REaLL), 2024)
These days, music has a huge impact on its listeners who come from a wide range of backgrounds. Sadly, very view listeners are aware of the hidden and implicit meanings contained in the song lyrics. Thus, investigating deixis found in Islamic music by Maher Zain is crucial to provide the listeners with precise interpretations. This current study attempts to discover the varieties of deixis found in lyrics of the songs by Maher Zain ("Thank You Allah” album). This library study used Mahar Zain’s English lyric transcripts of 16 songs as the object of the investigation. Several procedures were done to analyze the data, namely data reduction, data display, as well as drawing conclusion and verification. The results revealed five varieties of deixis found in Maher Zain’s Islamic songs, namely 191 data for place deixis, 43 data for relative-time deixis, 27 data for place deixis, and several names related to The Prophet Muhammad SAW that referred to social deixis. In this study, there was no data found related to absolute-time deixis.  These current findings are expected to give deeper understanding related to implied meanings of the artwork, especially song lyrics in which the song can be used as source of motivation in life.